Engaged disengagement: reframing as feminist critique in Vanessa Place's Tragodía. Issue 4 (7th June 2017) - Colby, Georgina
ABSTRACT: This essay positions Vanessa Place's Tragodía (2011) as an instance of reframing as contemporary feminist cultural critique. An enquiry into allegory, hermeneutics, and the performative use of indifference in Place's conceptual writing generates insights into new narrative conditions produced by Place's work. Tragodía does not represent trauma but rather generates trauma through a poetic practice that has a bipartite structure: conceptual writing (allegory) and Place's performances of the narratives. Place's performance is read in this analysis as an ancillary act of reframing that raises the question of what might be at stake in the performative use of indifference. Understood as a strategy of failure, Place's performance parallels the lack of mediation in the conceptual act of reframing. Positioned counter to the linguistic deformation of the subjects' speech acts and the erasure of affect that occurs in the legal narratives through the act of interpretation, the refusal to interpret implicit in the act of reframing in Tragodía is an ethical gesture, a paratextual pathway to metamorphosis. In its refusal to interpret, Tragodía creates a site of contextual resistance to the oppression of the subjects' organic narratives by the institutional language of the law, and offers a new textual field of meaning-making.